A novel GRAIL E3 ubiquitin ligase promotes environmental salinity tolerance in euryhaline tilapia - Fiol, Diego Fernando (2011)
Background: Tilapia (Oreochromis mossambicus) are euryhaline fishes capable of tolerating large salinity changes. In a previous study aimed to identify genes involved in osmotolerance, we isolated an mRNA sequence with similarity to GRAIL (Gene Related to Anergy In Lymphocytes), which is a critical regulator of adaptive immunity and development. Tilapia GRAIL contains a PA (protease associated) domain and a C3H2C3 RING finger domain indicative of E3 ubiquitin ligase activity. Scope of review: Western blots analysis was used to assess GRAIL expression pattern and responses to hyperosmotic stress. Immunohistochemistry was used to reveal the cellular localization of GRAIL in gill epithelium. Overexpression in HEK293 T-Rex cells was used to functionally characterize tilapia GRAIL. Salinity stress causes strong up-regulation of both mRNA and protein levels of tilapia GRAIL in gill epithelium. Tissue distribution of GRAIL protein is mainly confined to gill epithelium, which is the primary tissue responsible for osmoregulation of teleost fishes. Overexpression of tilapia GRAIL in HEK293 cells increases cell survival (cell viability) while decreases apoptosis during salinity challenge. Major conclusions: Our data indicate that tilapia GRAIL is a novel E3 ubiquitin ligase involved in osmotic stress signaling, which promotes environmental salinity tolerance by supporting gill cell function during hyperosmotic stress. General significance: Involvement of tilapia GRAIL in the osmotic stress response suggests that GRAIL E3 ubiquitin ligases play a broader role in environmental stress responses, beyond their documented functions in adaptive immunity and development.